TikTok use intensity and self-identity among high school students - Devi, Antika Sari; Sutejo, Sutejo; Slamet Riyanyo (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Adolescence is a crucial developmental stage in the formation of self-identity. During this phase, individuals strive to recognize their potential, values, and life goals through self-exploration and social interaction. The development of technology and social media, particularly TikTok, has become part of adolescents' daily lives. TikTok provides a space for expression, entertainment, and social interaction, but high usage intensity has the potential to influence the process of self-identity formation. Purpose: To determine the relationship between the intensity of TikTok use and adolescent self-identity. Method: A quantitative method with a correlational design and a cross-sectional approach. The study population included 360 students in grades 10 and 11 aged 15–18 years. A sample of 79 respondents was selected using a purposive sampling technique based on the criteria of active TikTok users for at least the past month. Results: Data were collected using a questionnaire and analyzed using the Spearman Rank correlation test (ρ). The results showed that the majority of respondents had high TikTok usage intensity and a strong self-identity. Conclusion: The p-value = 0.199 (p > 0.05) and rₛ = 0.146 indicated no relationship between the intensity of TikTok use and adolescent self-identity. Keywords: Self-Identity; Teenagers; TikTok Usage Intensity.